Violence in Commercial Sex Work: A Case Study on the Impact of Violence Among Commercial Female Sex Workers in India and Strategies to Combat Violence - Dasgupta, Satarupa (Violence against women, 2021)
Violence is one of the primary contextual factors that significantly raise sex workers’ sexually transmitted infection risk. The current study examines how violence affects sexual health behavior among commercial female sex workers in a red light district in Calcutta, India. The study which employs in-depth interviews of 37 commercial female sex workers also discusses an innovative multilayered strategy devised by the sex workers to combat violence through a community mobilization drive. The current study shows that the sex workers can confront the system that precipitates violence and actively engage with it to mitigate the impact of structural barriers to empowerment.